Experimental study of fatigue properties of orthotropic steel deck with U-shaped stiffeners. Issue 2 (11th April 2019) - Zeng, Yong; Tan, Hongmei; Zhong, Huadong; Yu, Qu
Abstract : A 1 : 2 scale fatigue experiment on an orthotropic steel deck was carried out to investigate the fatigue behaviour of the steel decks of a suspension bridge. The experimental model was developed from the orthotropic steel deck of a long-span suspension bridge in the Three Gorges reservoir area. The fatigue experiment involved 2·8 million load cycles. Up to 2 million load cycles, the stress data showed that the fluctuations in stress values were small and, in the loading and unloading processes, the displacements agreed very well and there was no local cracking or damage. The fatigue performance of the orthotropic steel deck thus met the design requirements and had enough safety reserve. After 2 million fatigue load cycles, the load value gradually increased. Cracks did not appear until 2·6 million cycles. Finally, after 2·8 million cycles, crack accumulation caused structural damage to the model. It can thus be concluded that, with good welding and normal maintenance, this orthotropic steel deck will not suffer fatigue cracks during its design working life. This work provides a theoretical and experimental basis for the practical construction of such bridges.